Oral intake management in laboring women: a scoping review - Zhu, Chenping; Zhou, Lin; Tang, Yongjie (Frontiers in Medicine, 2025)
Background and objectivesLabor is a physically demanding and painful process that may lead to fat breakdown, ketone accumulation, and ketosis, potentially resulting in metabolic acidosis. Proper management of oral intake during labor helps mitigate this risk. We reviewed the published impact of oral intake management during labor on maternal and neonatal outcomes.Methods and study designThe scoping review used Arksey and O′Malley’s methodological framework. The systematic search was conducted using PubMed, Web of Science, Embase, Cochrane Library, Scopus, CNKI, and CINAHL Complete databases in May 2025. The literature published in the database until May 2025 was searched.ResultsA total of 17 studies, involving 13,141 participants, were included in this review. Out of these, 15 studies were randomized controlled trials, and 2 were observational studies. The participants in this review were low-risk parturients without maternal illness. The oral intake during labor included carbohydrate-rich beverages, isotonic sports drinks, high-protein drinks, bicarbonate solutions, and other similar beverages. The outcomes of this review encompassed both maternal and neonatal outcomes. The review did not identify any significant harms associated with moderate oral intake.ConclusionModerate oral intake did not prolong labor duration in low-risk parturients and helped maintain energy expenditure during labor. It also stabilized blood glucose and electrolyte levels, preventing maternal hypoglycemia and ketoacidosis. However, due to concerns about aspiration and labor progress, a multidisciplinary approach and individualized dietary plan were essential to optimize the type and timing of intake. Generally, light carbohydrate diets were recommended in the early stages of labor, while high-protein and isotonic energy drinks might be more suitable during the second stage for low-risk women.Systematic review registrationhttps://osf.io/vmahc/overview.